An Analysis Of The Influence Of Employer Branding And Digital Hiring On Social Media Platforms On Generation Z's Job Intention, Using Reputation As A Mediator - Muna, Auliya Nailul; Irmawati, Irmawati (Community Engagement and Emergence Journal (CEEJ), 2025)
This research investigates how employer branding and digital hiring influence Generation Z’s intention to apply for jobs in the Solo Raya region, with corporate reputation acting as a mediating factor. The swift progression of digital technology has prompted organizations to adjust their recruitment approaches by enhancing their image and credibility via social media platforms. Being digital natives, Generation Z individuals often assess a company’s trustworthiness and reputation before submitting job applications. This study utilized a quantitative design, collecting data through an online questionnaire administered to 199 Generation Z participants in the Solo Raya area, selected using purposive sampling. The data were examined using Structural Equation Modeling (SEM) with Partial Least Squares (PLS), facilitated by SmartPLS software. The results reveal that both employer branding and digital hiring significantly and positively impact corporate reputation as well as Generation Z’s intention to apply for jobs. Nevertheless, corporate reputation does not mediate the effect of employer branding on job application intention. Conversely, it partially mediates the relationship between digital hiring and job application intention. These findings imply that cultivating a strong corporate reputation can amplify the impact of digital recruitment strategies in attracting young job seekers.